Pengungkapan Corporate Social Responsibility sebagai Pemoderasi Pengaruh Good Corporate Governance pada Nilai Perusahaan - Tamara, I Gusti Ayu Agung Tata Intan; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2020)
This research aims to obtain empirical evidence regarding the Corporate Social Responsibility disclosure as a moderating effect of Good Corporate Governance on firm value. Banking sector companies that participated in the CGPI ranking and listed on the Indonesia Stock Exchange in 2013-2017 are the object of this study. Moderated Regression Analysis (MRA) is a technical analysis of the data in this study. The results show that Good Corporate Governance has no effect on firm value and the Corporate Social Responsibility disclosure as a moderating variable is able to strengthen the effect of Good Corporate Governance on firm value. Keywords: Good Corporate Governance; Corporate Social Responsibility Disclosure;  Firm Value.